Bone Mineral Density Screening and the Frequency of Osteopenia/Osteoporosis in Turkish Adult Patients With Celiac Disease - Sayar, Süleyman; Aykut, Hüseyin; Kaya, Özkan; Kürbüz, Kemal; Ak, Çağatay; Gökçen, Pınar; Bilgiç, Nermin Mutlu; Adalı, Gupse; Kahraman, Resul; Doganay, Levent; Özdil, Kâmil (Turkish Journal of Gastroenterology, 2021)
Background: The aim of this study was to evaluate the prevalence of osteopenia and osteoporosis in adult patients with celiac disease (CD) at diagnosis and/or in the follow-up after a gluten-free diet (GFD). Methods: Adult patients diagnosed with CD were retrospectively screened through follow-up records and computer databases. Patients assessed by dual-energy X-ray absorptiometry (DEXA) at diagnosis and/or in the follow-up after a GFD were included in the study. Results: One hundred patients who underwent a DEXA scan at least once after diagnosis or after being on a GFD were included in the study. The mean age of the patients at diagnosis was 34.61 ± 10.3 years, and 84% of the patients (n = 84) were female. At the time of diagnosis (n = 46), the prevalence of osteopenia and osteoporosis was 67.3% and 15.2%, respectively, at the lumbar spine, and 43.4% and 10.8%, respectively, at the femur. After a GFD (n = 78), the prevalence of osteopenia and osteoporosis was 61.5% and 8.9%, respectively, at the lumbar spine, and 37.1% and 2.5%, respectively, at the femur. Conclusion: The prevalence of CD patients with low bone mineral density (BMD) is high after diagnosis and in the follow-up after a GFD. It is important for all patients with CD to undergo a DEXA scan to determine the follow-up and/or treatment characteristics. Cite this article as: Sayar S, Aykut H, Kaya Ö, et al. Bone mineral density screening and the frequency of osteopenia/osteoporosis in Turkish adult patients with Celiac disease. Turk J Gastroenterol. 2021; 32(7): 600-607.